Pt- AND Pd-CATALYSTS ON MODIFIED KAOLINITES IN THE REACTION OF N-HEXANE ISOMERIZATION - N.A. Zakarina; N.A. Kornaukhova; R.Toktassyn (Academic Scientific Journal of Chemistry, 2019)
The article presents the data on synthesis and properties of Pt and Pd catalysts supported on modified Ti4+ and Zr4+ kaolinites of two of Kazakhstan fields- Sarymsak, Ermakov (KS and KE), their catalytic activity in nhexane isomerization, depending on temperature and composition of the catalyst. The elemental and phase composition of the synthesized catalysts, as well as their textural properties, are determined. It was indicated that the studied catalysts showed high activity and selectivity in the reaction isomerization of n-hexane with formation of mono- and disubstituted isohexanes and isoheptanes. The Pt catalysts supported on modified Zr4+ and Ti4+ kaolinites were exhibit higher isomerization activity compared to Pd-catalysts. Maximum conversion of n-hexane, equal to 43.2% and a yield of C6 + C7 isomers of 36.0% with selectivity for isomers of 93.3%, was observed on 0.35% Pt / Zr (5.0) HKS catalyst at 400 °C which can be recommended for further improvement.